Cathodal Transcranial Direct Current Stimulation Over the Right Temporoparietal Junction Suppresses Its Functional Connectivity and Reduces Contralateral Spatial and Temporal Perception - Dalong, Guo; Jiyuan, Li; Yubin, Zhou; Yufei, Qin; Jinghua, Yang; Cong, Wang; Hongbo, Jia (Frontiers in Neuroscience, 2021)
The temporoparietal junction plays key roles in vestibular function, motor-sensory ability, and attitude stability. Conventional approaches to studying the temporoparietal junction have drawbacks, and previous studies have focused on self-motion rather than on vestibular spatial perception. Using transcranial direct current stimulation, we explored the temporoparietal junction’s effects on vestibular-guided orientation for self-motion and vestibular spatial perception. Twenty participants underwent position, motion, and time tasks, as well as functional magnetic resonance imaging scans. In the position task, cathodal transcranial direct current stimulation yielded a significantly lower response in the -6, -7, -8, -9, -10, -11, and -12 stimulus conditions for leftward rotations (P < 0.05). In the time task, the temporal bias for real transcranial direct current stimulation significantly differed from that for sham stimulation (P < 0.01). Functional magnetic resonance imaging showed that cathodal transcranial direct current stimulation suppressed functional connectivity between the temporoparietal junction, right insular cortex, and right supplementary motor area. Moreover, the change in connectivity between the right temporoparietal junction seed and the right insular cortex was positively correlated with temporal bias under stimulation. The above mentioned results show that cathodal transcranial direct current stimulation induces immediate and extended vestibular effects, which could suppress the functional connectivity of the temporoparietal junction and in turn reduce contralateral spatial and temporal perception. The consistent variation in temporal and spatial bias suggested that the temporoparietal junction may be the cortical temporal integrator for the internal model. Moreover, transcranial direct current stimulation could modulate the integration process and may thus have potential clinical applications in vestibular disorders caused by temporoparietal junction dysfunction.